A Design Process Framework and Tools for Teaching and Practicing Biomimicry - Benjamin Linder; Jean Huang (Biomimetics)
Few design methods exist that provide clearly structured, visually intuitive, and easily monitored scaffolding for navigating the considerable complexity of biomimetic processes. To this end, we present a holistic biomimicry process framework informed by design abstraction models that clarifies core skills involved and how they combine to form essential practices, such as biology-to-design and challenge-to-biology. The structure–function and conditions-conducive-to-life perspectives are facilitated, ensuring support for sustainability considerations. We pair this framework with two process tools that make biomimicry design moves explicit for learners, educators, and practitioners. We share examples of the use of these tools from an upper-level undergraduate engineering course in biomimicry. Our observations indicate that the framework and tools support process acquisition, design iteration, knowledge transfer, and sustainability integration in biomimicry education and practice by enabling common design behaviors such as variation, iteration, debugging, and reflection.